US foreign policy and the Horn of Africa - Woodward, Peter (Ashgate Pub., 2006)
Examining US involvement in the Horn of Africa, this volume addresses the relationship between the US and the Islamic movement in this region. It explores the interests of the United States in the region through two cases: Sudan and Somalia. It also discusses the effects of the Eritrean-Ethiopian war on US policy and posture in the region.